ANALISIS PENGARUH PENDIDIKAN, TINGKAT UPAH, DAN KESEMPATAN KERJA TERHADAP JUMLAH PENGANGGURAN TERDIDIK DI INDONESIA - Eliza, Eliza (Jurnal Ekobistek, 2016)
One of issue that be attention in activity periode of long time development was problem increase man power quality that enough to develop and in another said gotten problem specially about employment for example heigh educated unemployment  and work opportunity limited and not able to hold total of unemployment. Learn of this research that varians up and down independent variable (graduated from High School, University, free level and work opportunity) were effected see variable (total educated unemployment in Indonesia were 96,4%, and another was 3,6%. This was another factor that wasnot gotten in this model research. Another that graduated from High School, University, salary and work opportunity effect total educated unemployment in Indonesia very significant are 66,113. Based partial learning graduated from University and salary effected very significant were 2,623% and 2,507. In another part graduated from High Scholl and work opportunity have not significant effect to total unemployment in Indonesia were 0,304 and 0,689. Keyword: Education, Employment, Unemployment